Legitimization of Violence in the Political Discourse of Donald Trump and Benjamin Netanyahu during the Gaza War Press Conference - Farabi Nirmala; Agwin Degaf (Journal of Pragmatics Research, 2026)
Political discourse on Gaza often employs the language of peace to obscure practices of violence and domination. Within the broader field of discourse and ideology studies, this issue occupies a complex intersection between language, power, and moral justification, yet it remains underexplored as a collaborative construction between two state leaders speaking in a shared public forum. This article aims to examine how these leaders simultaneously deploy linguistic strategies to normalize warfare and legitimize coercion, rather than merely to produce persuasive or emotive speech. The study draws on qualitative data collected through content analysis of the video and transcript of a joint press conference, interpreted within Van Dijk’s critical discourse framework that maps ideological structures at both macro and micro levels. The findings reveal a carefully orchestrated combination of authority, numerical framing, disclaimers, national glorification, hyperbole, and lexical choices that portray the in-group as moral saviors while silencing the suffering of the out-group. Such discursive patterns divert global attention from humanitarian crises toward policies that primarily serve hegemonic interests, reinforcing domination through language. The article recommends strengthening public critical literacy, enhancing transparency in humanitarian reporting, and extending comparative studies across political contexts to better understand how discourse legitimizes violence in contemporary political communication.